PERLINDUNGAN HUKUM TERHADAP PEMBELA HAK ASASI MANUSIA PERSPEKTIF TEORI ALASAN PENGHAPUS PIDANA - Moch. Choirul Rizal (Arena Hukum, 2023)
Legal protection of human rights defenders in Indonesia is at an alarming point. This sociolegal study focused on the objective conditions of legal protection for human rights defenders and the legal protection for human rights defenders from a theoretical perspective on the reasons for erasers punishment. The results are human rights defenders still experience arrests, shootings, clashes and torture. There are also several criminal law policies that have the potential to violate the rights and guarantees of legal protection for human rights defenders. Second,